A procedure for the size, shape and topology optimization of transmission line tower structures. (15th March 2016) - Souza, Rafael Rodrigues de; Fadel Miguel, Leandro Fleck; Lopez, Rafael Holdorf; Miguel, Letícia Fleck Fadel; Torii, André Jacomel
Highlights: Constructive and prototype testing feasibility considered for topology optimization. Structural design constraints based on ASCE 10-97 recommendations. The topology optimization method allows the consideration of staggered bracing. Firefly algorithm and backtracking search algorithm employed and compared. Topology optimization achieved a weight reduction of over 6.4%. Abstract: This paper presents a methodology for topology optimization of transmission line towers. In this approach, the structure is divided in main modules, which can assume different pre-established topologies (templates). A general rule for the templates creation is also presented, which is based in terms of the design practice and feasibility of prototype testing. Thus, these allow that the optimal solution has an important characteristic of direct industrial application. Furthermore, during the optimization process the size and shape of the structure are optimized simultaneously to the topology choice. For numerical examples, two structures were assessed. The first one is a transmission line tower studied in CIGRÉ (2009). Eight different load cases were considered. The second one is a single circuit, self-supported 115 kV transmission line tower. The structure was subjected to a cable conductor rupture scenario and a wind load hypothesis. In both examples the constraints from the ASCE 10-97 (2000) were applied. Due to the non-convex nature of the problem and to the presence of discrete variables in the procedure, the optimization was conducted through the Firefly Algorithm (FA) and the Backtracking Search Algorithm (BSA), which are two modern heuristic algorithms. The results for the size, size and shape, and size, shape and topology optimization are presented and discussed, as well as an analysis of the performance of the algorithms. It is shown that the proposed scheme is able to reduce up to 6.4% of the structural weight, when compared to a classical size optimization procedure on original structures.